Process, features and applications of shape memory alloys - Liverman, Keith, editor (New York : NY Research Press, 2015)
Alloys, which when deformed can return to their original shape once heated are called shape memory alloys (SMA). The field of shape memory alloys over the past few years has evolved as a significant topic of study. The complexity of relationship between properties and structure has always interested researchers and is mostly associated with the fact that strong multidimensional interactions occur in these alloys. This is reflected by initial researches on thermal and mechanical induced phase transformations and also latest developments emphasizing on magnetically induced structural changes. Applications of shape memory alloys offer innovative aspects which have drawn significant industrial interest attributing to its singular behavioral characteristics. These have led to the subject of shape memory alloys acquiring a position of great interest for undergoing research and studies in various fields varying from crystallography and thermodynamics to mechanical evaluation of electrical and chemical properties. The book includes recent researches and studies in this field. It encompasses various aspects of shape memory alloys like processing, novel applications and relationship between structure and properties.